The Factors of Speaking Difficulties in New Students' of English Education Department - David Andrian; Mohammad Kurdi Wijaya; Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2023)
Speaking problems is a phenomenon of new students that we see today some new students are used to using their mother tongue, they tend to use their mother tongue because they have been familiar since childhood, so it is easier to talk to each other. They feel they lack mastery of foreign languages so they lack motivation. They are not so used to using foreign languages. From the explanation above, related to the theory of (Penny Ur, 1996 in Fitri Nurhadiah, 2019) there are four factors that cause students' difficulties in speaking such as barriers, nothing to say, low or uneven participation, and the use of mother tongue. Here, the author conducted research by using qualitative approach and implement observation and interview to get the data. there are 3 factors that cause difficulties for new students in speaking, namely performance conditions, learning environment, speech problems such as barriers, nothing to say, low or uneven participation, and use of mother tongue.